Historical Archaeology Through a Western Lens - Purser, Margaret Sermons; Warner, Mark S. (Book collections on Project MUSE., 2017)
"The mythic American West, with its perilous frontiers, big skies, and vast resources, is frequently perceived as unchanging and timeless. The work of many western-based historical archaeologists over the past decade, however, has revealed narratives that often sharply challenge that timelessness. Historical Archaeology Through a Western Lens reveals an archaeological past that is distinct to the region--but not in ways that popular imagination might suggest. Instead, this volume highlights a western past characterized by rapid and ever-changing interactions between diverse groups of people across a wide range of environmental and economic situations. The dynamic and unpredictable lives of western communities have prompted a constant challenging and reimagining of both individual identities and collective understandings of their position within a broader national experience. Indeed, the archaeological West is one clearly characterized by mobility rather than stasis. The archaeologies presented in this volume explore the impact of that pervasive human mobility on the West--a world of transience, impermanence, seasonal migration, and accelerated trade and technology at scales ranging from the local to the global. By documenting the challenges of both local community-building and global networking, they provide an archaeologyofthe West that is ultimatelyfromthe West"--Provided by publisher.